2021
DOI: 10.3389/feduc.2021.666792
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effectiveness of STEAM-Based Courses on Junior High School Students’ Scientific Creativity

Abstract: The purpose of this study is to explore the effectiveness of a STEAM (Science, Technology, Engineering, Arts, Mathematics) -based curriculum on junior high school students’ scientific creativity. The main topic of the STEAM-based curriculum in this study is an ancient mechanical clock that was designed and produced by the authors’ team. Further, the main concept of the ancient mechanical clock is about a gear wheel. Hence, this study designed two stages of courses which were gear wheel science courses (2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…One of the stages of developing creative thinking skills is through training in generating initial ideas, detailing the framework, and identifying concrete steps used to develop ideas (Leasa et al, 2021;Wijayati et al, 2019). The results of this research are in line with previous research which produced data that students obtained better grades and obtained higher scientific creativity scores after taking STEAM-based courses (Tran et al, 2021). Furthermore, the results of this study imply that a STEAM approach can help students maintain or continue their scientific creativity.…”
Section: Discussionsupporting
confidence: 87%
“…One of the stages of developing creative thinking skills is through training in generating initial ideas, detailing the framework, and identifying concrete steps used to develop ideas (Leasa et al, 2021;Wijayati et al, 2019). The results of this research are in line with previous research which produced data that students obtained better grades and obtained higher scientific creativity scores after taking STEAM-based courses (Tran et al, 2021). Furthermore, the results of this study imply that a STEAM approach can help students maintain or continue their scientific creativity.…”
Section: Discussionsupporting
confidence: 87%
“…The final product was assessed based on the creativity dimensions of resolution, elaboration, and novelty; 76% of the final product was categorized as good. In another study, Tran et al (2021) assessed the creativity of 63 junior high school students after designing an ancient mechanical clock with the concept of gears for four weeks. The results showed a significant change in students' creativity scores before and after the activity.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study by Tran et al (2021a) revealed that a curriculum based on science, technology, engineering, arts, and mathematics enhance learners' creativity. Moreover, technology in such curriculum can help students maintain education (Tran et al, 2021b). It has been argued that culture also shapes creativity to a great extent (Shao et al, 2019).…”
Section: Technologymentioning
confidence: 99%